Blockchain Applications in IoT Security - Patel, Harshita; Patel, Harshita, 1985-; Thakur, Ghanshyam Singh, 1976- (US: IGI Global, 2020)
"This book examines the role of blockchain technology in IoT generated data security issues"--
Includes bibliographical references and index.
Keywords: Internet of things -- Security measures; Blockchains (Databases)